Unmanned Aerial Surveillance System - Paul Ciprian PATIC (Communications of International Proceedings, 2025)
In this paper, one presents an Unmanned Autonomous Surveillance vehicle which has a wide range of applications in dangerous activities in the military or police. They are also frequently used in civilian areas for sports, social, or agricultural activities. The main reasons why one chose this topic are: the intersection of different research fields necessary for the realization of this project, such as aerodynamics, systems theory, electronics and programming, the usefulness of these systems in solving dangerous situations, autonomous drones represent the future in the development of human society and civilization.
Keywords: Drone; Microcontroller; Quadcopter; .PixyCam2; PID; PWM Signal; UAV; UAS.